Analysis of the dictionary definitions of the nominees of the concept «woman» in the dictionaries of the Kazakh, Russian and Chinese languages (Journal of Oriental Studies, 2017)
The article analyzes the concept of dictionary definitions of the nominees ‘woman’ in the dictionaries of the Kazakh, Russian and Chinese languages by component analysis allowed to find both similarities and differences in the semantic structure of the basic words.